Photocatalytic detoxification of aflatoxins in Sudanese peanut oil using immobilized titanium dioxide - Magzoub, R.A.M. (2019)
A study on the photocatalytic detoxification of aflatoxins in Sudanese peanut oil was performed using titanium dioxide (TiO2) that was immobilized on a glass support as the photocatalyst and a 500 W high-pressure lamp (with emitted UV of 920 W/m2 and visible of 2000 W/m2) as the light source. The study was performed on naturally contaminated peanut oil obtained from two different irrigation systems in Sudan. Aflatoxin B1 (AFB1) and aflatoxin B2 (AFB2) were identified, quantified and detoxified, whereas aflatoxin G1 (AFG1) and aflatoxin G2 (AFG2) were not detected. The results showed that photocatalysis was better than photolysis, whereby â¥99.4 of AFB1 and â¥99.2 of AFB2 were effectively detoxified within 4 min of irradiation at room temperature. In addition, there was no significant changes in the physicochemical characteristics of the peanut oil after treatment, these include fatty acids composition, peroxide value, saponification value, acid value, free fatty acids, iodine value, moisture and volatile matters as well as the refractive index. Furthermore, the TiO2 photocatalyst was also reusable for up to ten cycles of application, thus offering a practical way to detoxify aflatoxins in peanut oil. Â© 2018 Elsevier Ltd